APPROACHES TO TEACHING AND DEVELOPING WRITING SKILLS ABSTRACT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Writing is a foundational pillar of academic success and professional communication. This article explores various methodological approaches to teaching writing, moving beyond traditional product-oriented techniques to contemporary process and genre-based strategies. The study evaluates the effectiveness of integrating peer feedback and digital tools in enhancing student engagement and structural accuracy. By analyzing pedagogical shifts, the research aims to provide a roadmap for educators to develop robust writing competencies in learners.